Plantation farming of Cameron Highlands: towards promoting an innovative and sustainable agriculture in Malaysia - Karim, A.H.M Zehadul (International Institute for Private, Commercial and Competition Law, 2018)
Cameron Highlands is an enchanting mountainous region with steep slopes and hill peaks locating in Pahang State of Malaysia stretching between 1830 m above sea level containing a total land of 71,218 ha (see Aminuddin et al 2005). It possesses a tropical highland climate which pours sufficient rainfall to make a cool weather being perfectly suitable for sustainable plantation agriculture. With this atmospheric support and ecological suitability, there emerged a group of enthusiastic entrepreneurs with considerable ability who initiated an innovative agriculture in the region providing a business-oriented commercialised farming to produce multifarious fruits, flowers and vegetables meeting the national and international demands. Based on labour-intensive family farming, one conspicuous feature of these farms is that they employ a large number of foreign workers coming from the neighbouring South East Asian and South Asian countries who knew the intricacies of this type of cultivation. Consequently, the paper relied on empirical data collected in the form structured interviews of 10 farm managers and 200 foreign workers; conducted one FGD (Focus Group discussion), and also further depended on researcher’s own observation and informal reporting from a cross-section of people coming from the categories of local inhabitants, visitors and tourists thus making the research innovative and pragmatically significant. The paper discusses different aspects of Cameron agriculture narrating the various complicacies and challenges relating to this productive plantation farming which is economically useful to the stakeholders and the beneficiaries. The findings show that the entrepreneurs have been able to adapt by interacting and responding properly to the existing eco-environment of Cameron Highlands which has effectually kept alive a continuous economic and commercial activities in this region by providing an innovative and sustainable agriculture. The research however, cautions the overuse of chemical fertilizers bearing impact on human health for which it is suggested that chemical technification of cultivation should be minimized, and instead, the entrepreneurs should focus more on the pre-existing local skills with labour-intensive organic farming system of production.